Introduction to semiconductor materials and devices - Tyagi M S (New Delhi: Wiley, 2005)
This comprehensive introduction to the elementary theory and properties of semiconductors describes the basic physics of semiconductor materials and technologies for fabrication of semiconductor devices. Addresses approaches to modeling and provides details of measurement techniques. It also includes numerous illustrative examples and graded problems.
Include bibliographical references.; Appendices A-G, 637-656p.; Index 657-669p.
Keywords: Physics; Semiconductor devices; Semiconductor materials; Semiconductors; General Science